467 Anti-EGFR antibody added to ongoing anti-PD-1 antibody treatment for metastatic cutaneous squamous cell carcinoma of the face: two case reports. (9th November 2020) - Eton, Omar; Hsu, Emily; Patel, Akshay; Eton, Omar; Cartun, Richard; Earle, Jonathan; Mnayer, Laila; Yu, Peter; Kotowitz, Jennifer
Abstract : Background: Recurring cutaneous squamous cell carcinoma (SCC) remains an area of high unmet medical need. While anti-PD-1 antibodies are now approved for this diagnosis, more than half the patients will need more effective treatments, supporting the development of new or combination regimens. Weekly cetuximab targets EGFR and has anti-tumor immunogenic properties that could complement anti-PD-1 immunotherapy. Cetuximab is being evaluated in combination clinical trials. Panitumumab also targets EGFR but is felt to function as a signal transduction inhibitor with weaker anti-tumor immunogenic properties; however, this medication is dosed every two weeks rather than weekly and has a relatively favorable toxicity profile. Methods: Two consecutive elderly patients with significant comorbidities presented with a performance status of ECOG 3 and rapidly progressive recurrent cutaneous SCC of the face. The patients were presented treatment with an anti-PD-1 antibody, with an option - were there an inadequate palliative response - to include an EGFR antibody provided tolerance was adequate and molecular markets supported so doing. Each patient signed consent for treatment and consent for photographs. Dosing was per package insert, starting conservatively with pembrolizumab 2 mg/kg or nivolumab 3 mg/kg, respectively, escalating in both cases to flat dosing once it was apparent that tolerance was acceptable. The first cycle of panitumumab (6 mg/kg), when needed to be invoked, was administered solo between two cycles of PD-1 inhibitor, then every two weeks while the PD-1 inhibitor continued every two - four weeks. Results: A 78 year old women with significant cardiac disease and a St Jude tissue aortic valve, had undergone prior surgeries and radiation therapy for her recurring SCC of the face followed then by major resection, parotidectomy, flap reconstruction, and supraomohyoid neck dissection; only two weeks after the latter surgery, she presented with over 20 new in-radiation field metastases (see photo below). A 90 year old woman with emphysema on home oxygen and living in a facility presented with diffuse local recurrence 4 months after orbital exenteration, parotidectomy, neck dissection, and flap. Both patients' tumors were characterized: PDL1 (clone E1L3N) 2% and 10%, respectively; scant peritumoral or intratumoral lymphocytes; tumor mutation burden high (33 and 30 mutations per megabase, respectively); epidermal growth factor receptor (EGFR) high 3+ by IHC, but with no gene mutations detected in EGFR, kras or nras; microsatellite stable. In the 78 yo woman, after two cycles of pembrolizumab, the 5 mm pink nodules grew further to up to 3 cm with facial erythema, edema, sealing the eye closed. Only by criteria was this not considered pseudoprogression, Panitumumab was integrated between cycles 2 and 3, resulting in a dramatic abrupt response: the masses became centrally necrotic, flaking, pouring off her face with prompt resolution in edema and complete response (CR) within 2 months - now lasting over 18 months - a period during which pembrolizumab and panitumumab were continued for 27 and 26 cycles respectively). Her major toxicity was diffuse erythema involving 30% of her torso; this resolved early on with triamcinolone 0.1% cream. She also developed scabs in her uninvolved scalp - some where other squamous and basal carcinomas had previously been resected and these all healed slowly (see photo), suggesting we were preventing similar future cancers from emerging in these areas. Similarly, the 90 yo woman achieved only a mixed response to nivolumab over 3 months with shrinking level V neck node but continued stubborn diffuse disease over her face and into the exenteration field. When panitumumab was added, however, there was clear improvement (See photo). With each of eight cycles, prolific crusting/scabbing would occur, shed, and reoccur, some in areas of the face without visible tumor, Mild acneiform rash and mild hypomagnesemia were readily managed. Her performance status and appetite improved and she gained back 14 pounds. After only 6 months, with pathologically confirmed CR, treatment had to be held because she was restricted to her assisted living facility in the midst of the COVID-19 pandemic. Now after a year, the remaining scabs are largely gone (see photo). Conclusions: The excellent tolerance of multiple cycles of out-patient combination treatment in these two consecutive patients with the same diagnosis, coupled with the observed durable anti-tumor clinical activity lasting now over a year - all support further exploration of panitumumab in combination with anti-PD-1 antibody treatment. A randomized trial would be needed to establish whether outcomes are truly better with the combination. Deciding on hyperprogression v pseudoprogression while getting anti-PD-1 antibody treatment remains a challenge. Laboratory studies would evaluate how such specific signal transduction inhibition by panitumumab might interfere with immune suppressive mechanisms in metastases, rendering them more sensitive to an induced anti-tumor cellular immune response by an anti-PD-1 antibody. Finally such combination treatment should help reduce the need for increasingly cosmetically and functionally altering surgeries. Ethics Approval: 'Per our Hartford Health Care IRB, case series of three or less patients does not constitute research.' Consent: Written informed consent was obtained from the patient for publication of this abstract and any accompanying images. A copy of the written consent is available for review by the Editor of this journal. References: Chen A1, 2, Ali N3, 4, Boasberg P5, 6, Ho AS7, 8. Clinical Remission of Cutaneous Squamous Cell Carcinoma of the Auricle with Cetuximab and Nivolumab. J Clin Med 2018 Jan 10;7(1). pii: E10. Foote MC, McGrath M, Guminski A, Hughes BG, Meakin J, Thomson D, Zarate D, Simpson F, Porceddu SV Phase II study of single-agent panitumumab in patients with incurable cutaneous squamous cell carcinoma. Ann Oncol 2014 Oct;25(10):2047–52. Ferris RL, Gillison ML, Harris J, et al. Safety evaluation of nivolumab concomitant with cetuximab-radiotherapy for intermediate and high-risk local-regionally advanced head and neck squamous cell carcinoma (HNSCC): RTOG 3504. Oral presentation at: 2018 ASCO Annual Meeting; June 1–5, 2018; Chicago, IL. Jong Chul Park, Lori J. Wirth, Keith Flaherty, Donald P. Lawrence, Shadmehr Demehri, Stefan Kraft, Immune checkpoint inhibition in advanced cutaneous squamous cell carcinoma: Clinical response and correlative biomarker analysis. Journal of Clinical Oncology 36, no. 15_suppl (May 20 2018) 9564. FDA approves pembrolizumab for cutaneous squamous cell carcinoma. FDA website. Published June 24, 2020. fda.gov/drugs/drug-approvals-and-databases/fda-approves-pembrolizumab-cutaneous-squamous-cell-carcinoma. Edith Borcoman, MD, Amara Nandikolla, MD, Georgina Long, BSc, PhD, MBBS, FRACP, Sanjay Goel, MD, and Christophe Le Tourneau, MD, PhD. Patterns of Response and Progression to Immunotherapy American Society of Clinical Oncology Educational Book 38 (May 23, 2018) 169–1787. Migden MR, Rischin D, Schmults CD, Guminski A, Hauschild A, Lewis KD, Chung CH, Hernandez-Aya L, Lim AM, Chang ALS, Rabinowits G, Thai AA, Dunn LA, Hughes BGM, Khushalani NI, Modi B, Schadendorf D, Gao B, Seebach F, Li S, Li J, Mathias M, Booth J, Mohan K, Stankevich E, Babiker HM, Brana I, Gil-Martin M, Homsi J, Johnson ML, Moreno V, Niu J, Owonikoko TK, Papadopoulos KP, Yancopoulos GD, Lowy I, Fury MG. PD-1 Blockade with Cemiplimab in Advanced Cutaneous Squamous-Cell Carcinoma. N Engl J Med 2018 Jul 26;379(4):341–351. Eve Maubec, Marouane Boubaya, Peter Petrow, Nicole Basset-Seguin, Jean-Jacques Grob, Brigitte Dreno, . Pembrolizumab as first line therapy in patients with unresectable squamous cell carcinoma of the skin: Interim results of the phase 2 CARSKIN trial. Journal of Clinical Oncology 36, no. 15_suppl (May 20 2018) 9534. Burtness B, et al . First-line pembrolizumab a new standard for recurrent, metastatic head and neck squamous cell carcinoma. Abstract LBA8_PR. Presented at: European Society for Medical Oncology Congress; Oct. 19–23, 2018; Munich. 10. Teruki Yanagi, * Shinya Kitamura, and Hiroo Hata. Novel Therapeutic Targets in Cutaneous Squamous Cell Carcinoma. Front Oncol 2018; 8: 79.